Simulation Pedestrian Flow Under Vertical Bottleneck Constraints: How Stair Configuration Affects Pedestrian Movement Efficiency - Wang, Jianyu; Ma, Jian; Sarvi, Majid; Alhawsawi, Abdullah; Lin, Peng; Yang, Mei-Cheng (Collective Dynamics, 2022)
As a result of the geometric constraints of the stairs, pedestrian movement features on stairways are different from level ambulation. Therefore, it is necessary for us to consider the stairs’ three-dimensional geometry when we try to explore how the stair configuration affects pedestrian movement efficiency. Based on the pedestrian fundamental features from a previous pedestrian single-file movement experiment on stairs, we investigated pedestrian flow under various stair configurations with an improved agent-based model. Our simulated indicates that both stair inclinations and tread depth of stair step are sensitive to the pedestrian dynamic on stairs. Generally speaking, pedestrian flow decreases with the increasing slope of stairs. When the stairs slope increased 5, 10, 15 and 20 degree, the evacuation efficiency dropped 5.8%, 12.8%, 19.3% and 28.4%. Besides, the effect of the tread depth on pedestrian total evacuation time is not changed monotonously. Scenarios with 0.3m tread depth size present the optimal evacuation efficiency. Other scenarios differ from 3% to 27.9% in terms of the total evacuation time.